The transformation universities - Krajewska, Anna (Studia Ecologiae et Bioethicae, 2012)
The subject of analyses in this study are the transformations taking place within universities as a result of the changing political, social, economic, and cultural conditions in past centuries. There is a description of the development of universities in the Middle Ages as well as of their transformation in the 14th-16th centuries. Their 19th-century development has also been analysed, with special attention being paid to German, British and American university institutions. The interwar period has also been taken into consideration. Another area of interest is the political, social and economic conditions which have brought about the development and transformation of universities at the turn of the 21st century.entury.